Chaetotaxy and morphometry of the head capsule and head appendages of the genus Derallus Sharp (Coleoptera: Hydrophilidae) - Rodriguez, Georgina; Torres, Patricia L. M.; Archangelsky, Miguel (Zootaxa, 2020)
The primary and secondary chaetotaxy of the head capsule and head appendages of the three larval instars of the water scavenger beetle genus Derallus Sharp are described for the first time based on two species: D. angustus Sharp and D. paranensis Oliva. Morphometric characters derived from the head capsule and mouthparts are included, together with detailed illustrations of all characters. Chaetotaxy of these larvae is compared with that of Regimbartia attenuata (Fabricius), another species belonging to the Derallus-clade of Berosini.